2008
DOI: 10.1136/emj.2008.058792
|View full text |Cite
|
Sign up to set email alerts
|

Management of penetrating neck injury in the emergency department: a structured literature review

Abstract: The current literature suggests that prehospital cervical immobilisation may not be necessary unless the patient has focal neurological deficits. Studies show that patients with penetrating neck trauma who are haemodynamically stable and exhibit no "hard signs" of vascular injury may be evaluated initially by MDCT imaging even when platysma violation is present. Airway management is evolving, but traditional laryngoscopy continues to be the mainstay of airway stabilisation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
66
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(68 citation statements)
references
References 33 publications
1
66
0
1
Order By: Relevance
“…The literature suggests that spinal immobilization should be considered only in cases of PNI when the mechanism of injury and/or physical findings suggest spinal cord involvement. [18][19][20][21][22][23] Rapid sequence intubation (RSI) can be considered in cases where the airway is felt to be threatened but normal anatomy and structure relationship are well preserved. 18,24,25 In a retrospective study of more than 700 patients with PNI, Mandavia and colleagues found RSI to be safe and effective, with all of the 39 patients successfully intubated in this manner, compared to awake fibre-optic intubation, which was successful in 9 of 12 patients (three failures being rescued with RSI).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The literature suggests that spinal immobilization should be considered only in cases of PNI when the mechanism of injury and/or physical findings suggest spinal cord involvement. [18][19][20][21][22][23] Rapid sequence intubation (RSI) can be considered in cases where the airway is felt to be threatened but normal anatomy and structure relationship are well preserved. 18,24,25 In a retrospective study of more than 700 patients with PNI, Mandavia and colleagues found RSI to be safe and effective, with all of the 39 patients successfully intubated in this manner, compared to awake fibre-optic intubation, which was successful in 9 of 12 patients (three failures being rescued with RSI).…”
Section: Discussionmentioning
confidence: 99%
“…[18][19][20][21][22][23] Rapid sequence intubation (RSI) can be considered in cases where the airway is felt to be threatened but normal anatomy and structure relationship are well preserved. 18,24,25 In a retrospective study of more than 700 patients with PNI, Mandavia and colleagues found RSI to be safe and effective, with all of the 39 patients successfully intubated in this manner, compared to awake fibre-optic intubation, which was successful in 9 of 12 patients (three failures being rescued with RSI). 24 Although the results of this study would seem to support the safety of RSI in PNI, they may not apply to the 10% of patients with PNI who have a primary airway injury, 5 a subset that may not be identified on initial presentation.…”
Section: Discussionmentioning
confidence: 99%
“…8 However, recent literature supports the use of physical examination as a reliable tool for ruling in and out serious injuries from PNI. [1][2][3][4]6,9 Serial physical examination with auscultation of the carotid arteries is reported to be 95% sensitive 6 for ruling out major injuries and may be as high as 100% specific. 10,11 The largest and most relevant studies on the role of physical examinaton in stable PNI are outlined in Table 2. 1.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 The anatomy of the neck is complex, and many vital structures reside in close proximity, sometimes within millimetres, to one another ( Figure 1). …”
mentioning
confidence: 99%
“…The car suddenly slowed and the cyclist was thrown into the car by the rear window. Bystanders extricated him and a severe bleeding from a penetrating injury of right zone 1 of the neck started [7]. Hemorrhage was suddenly controlled by direct compression while an ambulance and HEMS were on the way.…”
Section: Case Presentationmentioning
confidence: 99%